Composition of the Volatile Oils of Anthemis coelopoda var. coelopoda from Turkey - Doğan, Gülden; Demirpolat, Azize; Bağcı, Eyüp (My University, 2015)
In this study, hydro distilled essential oils derived from the aerial parts of Anthemis coelopoda var. coelopoda (Asteraceae) grown in Turkey were analysed by GC and GC-MS system. Fifty seven components were identified representing 90.7% of the oils. It was determined that Anthemis coelopoda var. coelopoda essential oil contained b-caryophyllene (21.8%), nerolidol (10.8%), azulene (9.5%), borneol (5.5%), linalool (4.3%) and cyclopentadecane (4.2%) as major compounds. Essential oil analysis of the Anthemis coelopoda var. coelopoda has shown that it has b-caryophyllene/nerolidol and azulene chemotype.
Keywords: Biyoloji; Bitki Bilimleri